2017
DOI: 10.1249/mss.0000000000001338
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Moderates Glycemic Responses to Sitting and Light Activity Breaks

Abstract: Individuals with low CRF gained the most metabolic benefit from breaking prolonged sitting with regular bouts of light walking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 24 publications
5
27
0
Order By: Relevance
“…The aim of the intervention will be to promote and maintain at least a 60 min per day reduction in daily sitting time compared to usual practice at 24 months. Recent experimental evidence has demonstrated a reduction in glucose, insulin and blood pressure following regular standing and walking breaks (i.e., every 20–30 min), with total reductions in sitting varying from 28 min to 60 min across the course of a day [ 12 , 13 , 15 , 16 , 18 ]. Furthermore, using statistical modelling we have observed that interchanging 30 mins/day of sitting (measured with the activPAL) with standing and stepping is associated with favourable differences in insulin sensitivity [ 9 ] and inflammation [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the intervention will be to promote and maintain at least a 60 min per day reduction in daily sitting time compared to usual practice at 24 months. Recent experimental evidence has demonstrated a reduction in glucose, insulin and blood pressure following regular standing and walking breaks (i.e., every 20–30 min), with total reductions in sitting varying from 28 min to 60 min across the course of a day [ 12 , 13 , 15 , 16 , 18 ]. Furthermore, using statistical modelling we have observed that interchanging 30 mins/day of sitting (measured with the activPAL) with standing and stepping is associated with favourable differences in insulin sensitivity [ 9 ] and inflammation [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…These links between sedentary behaviour and health and work related outcomes are important because the estimated costs of presenteeism and absenteeism in the United Kingdom are reported to be more than £30bn ($39bn; €34bn), with presenteeism costing over twice as much as absenteeism. 14 More positively, reductions in sitting and breaking up sitting through standing and walking in acute experimental settings have led to improvements in important cardiometabolic markers of health such as glucose and insulin levels and blood pressure, 15 16 17 18 19 20 21 22 and feelings of fatigue and vigour. 23 24 …”
Section: Introductionmentioning
confidence: 99%
“…Sitting is a typical way to relax and get efficient storage of energy in a short time 1 . As a common type of sitting behavior, sedentariness refers to any sitting behavior with an energy expenditure ≤1.5 metabolic equivalents 2 .…”
Section: Introductionmentioning
confidence: 99%